Evaluation of Air Pollution Tolerance Index (APTI) by two species of terrestrial plants in some stations within Babylon Province, Iraq (Baghdad Science Journal, 2025)
This study deals with air pollution tolerance index (APTI) and anatomical variation in leaves of two species of terrestrial plants Ficus sp. and Conocarpus sp. that have bee commonly the separated along roadsides in many stations within Babylon province. APTI values of both species were less than 10 during study period which represented sensitivity of these plants to air pollution. There are Anatomical responses to pollution in the leaves of both studied species. Main adaptations included increased thickness of parenchyma cell walls with clear dark deposits in sections of Ficus sp. from sections of stations 2 and 4 which represent polluted stations. Conocarpus sp. main adaptation included stomata increased in density and decreased in size with high tannin cells content in heavy polluted station.